Electrophoretic Protein Banding Patterns among Penicillium Strains Isolated from Saudi Arabia - Kamel, Ehab Abdel-Razik; Rashed, M. Elsayed (International Journal of Applied Sciences and Biotechnology, 2014)
14 strains of Penicillium species were isolated from different localities and habitats from Jeddah, Saudi Arabia and cultivated on two different media: Czapek Dox’s medium, in which NaNO3 is the source of inorganic nitrogen, and Waksman’s medium, in which pepton is the source of organic nitrogen. Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis (SDS-PAGE) technique was used in this study to distinguish these isolates. The Penicillium isolates examined in this study consisted of six Penicillium species: Penicillium corylophilum (three isolates), P. rubrum (one isolate), P. citrinum (two isolates), P. crustosum (one isolate), P. canesens (six isolates) and Penicillium sp. (one isolate). The electrophoretic protein patterns from Penicillium isolates grown on Czapek Dox's medium revealed the presence of 17 different bands (out of 14 polymorphic bands, there were three monomorphic bands and two unique bands). The electrophoretic protein pattern of the same isolates grown on Waksman's medium revealed the presence of 12 different bands (out of eight polymorphic bands, there were four monomorphic bands and one unique band). Data were analysed by a clustering method and similarity coefficients using NTSYSpc version 2.02i. Two different phenograms were produced for the studied Penicillium species based on the analysis of the protein banding patterns. Data from the protein banding patterns produced from both media were combined and analysed to produce third phenogram, and the relationships between the species and isolates are discussed. DOI: http://dx.doi.org/10.3126/ijasbt.v2i3.10949 Int J Appl Sci Biotechnol, Vol. 2(3): 283-290